2021
DOI: 10.3390/ijerph18010328
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Biological Maturation, Physical Fitness, and Kinanthropometric Variables of Young Athletes: A Systematic Review and Meta-Analysis

Abstract: There is a growing interest in knowing the relationship between biological maturation and sport performance-related variables of young athletes. The objective of this study is to analyze the relationship between biological maturation, physical fitness, and kinanthropometric variables of athletes during their growing period, according to their sex. The systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement and the search protocol was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
2
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 86 publications
0
48
2
13
Order By: Relevance
“…The differences between chronological age and bone age suggest an advanced maturity at the top selection level with a larger effect size in male (1.8 years) vs. female (0.9 years) players. This is a well-known phenomenon in youth sport [ 36 ] and again emphasizes the advantage of early maturity during the selection. It is noteworthy that, despite the differences in relative age, the bone age did not differ between the semester groups except in a very few cases in the S4 group for girls.…”
Section: Discussionmentioning
confidence: 95%
“…The differences between chronological age and bone age suggest an advanced maturity at the top selection level with a larger effect size in male (1.8 years) vs. female (0.9 years) players. This is a well-known phenomenon in youth sport [ 36 ] and again emphasizes the advantage of early maturity during the selection. It is noteworthy that, despite the differences in relative age, the bone age did not differ between the semester groups except in a very few cases in the S4 group for girls.…”
Section: Discussionmentioning
confidence: 95%
“…The present study is not free of limitations. Among the most important limitations are the descriptive and cross-sectional nature of the study, a relatively small sample size, the age of the participants, which together with the design of the study does not allow us to analyze the evolution of the phenomenon studied throughout the entire maturation stage, and the method of estimating biological maturation, which although it is a widely used method in sports science [ 8 ], is not the hand and wrist X-ray, considered the gold standard for the calculation of the maturity offset [ 9 ]. Future research could evaluate the influence of age, biological maturation, and birth quartile on the differences between boys and girls in kinanthropometric and physical fitness variables in volleyball from the age of sports initiation to advanced stages of adolescence, using longitudinal designs, with a larger sample, to know the evolution of the differences throughout the growth stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, this characterization of the requirements of athletes during puberty must be undertaken with caution due to the effect that biological maturation has been shown to have on kinanthropometric and physical fitness variables [ 7 , 8 ]. More specifically, there is evidence of the different rates of maturation experienced by adolescents during the process, with these differences affecting the physical manifestation of the changes inherent to adolescence [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pullen et al (2022) found a relationship of change in maturity with standing long jump performance in girls [ 27 ]; Živković et al (2022) found that a significant interaction of gender and biological maturity was noted for countermovement jump [ 28 ]; and in Albaladejo-Saura (2022) as a maturity compensation difference between the genders of adolescent volleyball players related to the physical capacities of power and strength in boys and flexibility in adolescent girls [ 29 ]. Likewise, in a meta-analysis carried out by Albaladejo-Saura et al [ 30 ] that included 13 studies, early maturers had higher physical fitness.…”
Section: Discussionmentioning
confidence: 99%